Binding thiourea derivatives with dimethyl methylphosphonate for sensing nerve agents. Issue 19 (5th April 2019) - Chung, You Kyoung; Ha, Seonggyun; Woo, Tae Gyun; Kim, Young Dok; Song, Changsik; Kim, Seong Kyu
Abstract : Binding energies and geometries of 1 : 1 complexes formed between nerve agent simulant DMMP and 13 thiourea derivatives (TUn) were calculated and compared with the sensing efficiencies of TUn from QCM analysis. Abstract : In an effort to develop efficient substrates to sense organophosphonate nerve agents, we used the density-functional theory calculations to determine binding energies and geometries of 1 : 1 complexes formed between dimethyl methylphosphonate (DMMP) and 13 thiourea derivatives (TUn), including four newly-synthesized ones (n =10–13 ). The four new thiourea derivatives have a 3, 5-bis-(trifluoromethyl)phenyl group as one N -substituent and an alkylphenyl group with zero to three methylene linkages as the other N -substituent. The calculated geometries show that intermolecular double H-bonding is the most important factor influencing the formation of stable complexes at the molecular level. When the calculated binding energies were compared with the receptor efficiencies of the corresponding TUn substrates in a quartz crystal microbalance (QCM), a high degree of correlation was found. However, deviations from the correlation trend were found for a few TUn. We explained the deviations with a series of real time diffuse reflectance IR spectra as well as the calculated geometries. The most efficient receptor, determined from the QCM analysis and the IR spectroscopy, was TU13, in which three methylene linkages may provide an extra flexibility in the side chain. However, the calculated binding energy of the TU13 complex was small as a folded geometry of the bare TU13 hindered the double H-bonding. In contrast, the TU13 molecules in the QCM and the IR analyses may exist in unfolded geometries that are ready to form the double H-bonding.